Effect of water temperature on concrete properties - Naganathan S.; Mustapha K.N. (Jordan University of Science and Technology, 2023)
Compressive strength; Concrete mixtures; Concretes; Curing; Hammers; High temperature effects; Light velocity; Temperature; Casting temperatures; Concrete productions; Concrete properties; Good quality concrete; Properties of concretes; Quality of concrete; Rebound hammers; Ultrasonic pulse velocity; Water absorption